PERAN DANA ZAKAT DALAM MENGURANGI KETIMPANGAN PENDAPATAN DAN KEMISKINAN - Nova Rini; Nurul Huda; Yosi Mardoni; Purnama Putra (EKUITAS (Jurnal Ekonomi dan Keuangan), 2013)
This research attempts to examine the role of zakat in reducing income inequality and poverty, by taking a case study in Bogor. Two zakat institutions, Baytul Maal Bogor and Baytul Ikhtiar have been selected. A number of well-known inequality and poverty measures have utilized including Lorenz Curve, Gini coefficient, Atkinson index, headcount ratio, poverty gap index, income gap index, sen index and FGT index. After analyzing 200 household as the respondent, this study found zakat has increased monthly income of the household 11,48%. In general, the presence of zakat helps lower the income inequality an average of 0,3% points. The findings suggest that the presence of zakat has make better the income loss of the respondent  an average of 25,7% points. The existence of zakat is able to decrease the poverty incidence an average of 44% points. The gap of poverty can be reduced as the poverty gap show can be reductions of 27%. The depth of poverty can be reduced as the income gap show the reductions 18,8% points. Similarly, the severty of poverty can also be lower as evidenced from 18% points increase in the Sen index and 10% points increase in the FGT index.